ANALISIS PENGARUH JUMLAH WISATAWAN, KENDARAAN YANG PARKIR DI TEMPAT WISATA DAN TINGKAT HUNIAN KAMAR TERHADAP PENDAPATAN SEKTOR INDUSTRI PARIWISATA DI KOTA SURABAYA - WULANDARI, NURMA FITRI (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRACTEvery local government strives to improve its own regional economy including increasing the acquisition of local revenue (PAD) with one of the Tourism Revenues. One of the efforts to increase the Revenue of Tourism Industry Sector is to optimize the potential of tourism. Successful development in the tourism sector means increasing its role in local revenue, where tourism is the main component by taking into account factors that affect such as: Number of Tourists, Vehicles Who Parked at a Place of Attraction and Room Residential Level.Types and Sources of data use Secondary data in the form of time series data Period Year 2010-2016, Variable Research consists of Dependent Variable that is Tourism Industry Sector Ratio (Y), Independent Variable is Number of Travelers (X1) Vehicle Parking In Place Of Attraction (X2) Residential Room (X3). Data analysis tool using Multiple Linear Regression Method t test, Test f and Coefficient of Determination (R2).The result of the research shows that the variable of the number of tourists (X1) and the occupancy rate (X3) has an influence on the tourism industry sector income in the city of Surabaya (Y), the parking vehicle in the tourist place (X2) is the only variable that has no effect on the sector revenue Tourism Industry Di Kota Surabaya (Y)Â Keyword : Total Tourists, Parking Vehicles In Tourists, Levels of Rooms and Revenue Tourism Industrial Sectors